Early objective response may not be a prognostic factor of survival for patients with metastatic urothelial carcinoma: from a retrospective analysis of a cohort of 113 patients. Issue 1 (December 2015) - Roubaud, Guilhem; Brouste, Véronique; Beuzeboc, Phillipe; Fléchon, Aude; Tosi, Diego; Lavau-Denes, Sandrine; Chevreau, Christine; Culine, Stéphane; Oudard, Stéphane; Quivy, Amandine; Pourquier, Philippe; Houédé, Nadine
Abstract Background This study aims to better define prognostic factors for patients with metastatic urothelial carcinoma (mUC), and to identify patients who will benefit from first-line cisplatin-based chemotherapy. We test the hypothesis that early objective response (EOR), defined as the occurrence of an objective response following 2 or 3 courses of chemotherapy, could be a prognostic factor for overall survival (OS) and thus be used to guide treatment decisions. Data from 113 patients with evaluable mUC receiving first-line cisplatin-based treatment between January 2004 and December 2006 was collected retrospectively from prospectively-maintained databases across seven French cancer centers. Clinical factors potentially associated with survival and EOR were analyzed in univariate and multivariate analysis. Results One hundred three patient records were complete and available for inclusion in the multivariate model. Four factors were independently associated with OS: Performance status 1 and 2 (HR 2.3 [95 % CI 1.3–3.9], p = 0.002; HR 3.4 [95 % CI 1.6–7.2], p = 0.001 respectively); presence of visceral metastases (HR 2.2 [95 % CI 1.3–3.9], p = 0.004); abnormal hemoglobin levels (HR 1.7 [95 % CI 1.01–2.8], p = 0.045); disease progression (HR 10.1 [95 % CI 4.2–24.1], p < 0.001). Conclusions This study confirms the prognostic factors previously reported in first-line chemotherapy for mUC. However, we failed to demonstrate that EOR was an independent predictive factor of OS. Nevertheless, an early response evaluation is recommended since early progression is an important parameter that can be used to decide whether treatment should be interrupted and changed for alternative strategies integrating the concept of personalized medicine or new immune therapies.